Vertical stress history and paleoburial in foreland basins unravelled by stylolite roughness paleopiezometry: Insights from bedding-parallel stylolites in the Bighorn Basin, Wyoming, USA. (July 2020) - Beaudoin, Nicolas; Lacombe, Olivier; Koehn, Daniel; David, Marie-Eléonore; Farrell, Natalie; Healy, David
Abstract: We apply the stylolite roughness inversion technique on sedimentary, bedding-parallel stylolites hosted in the Paleozoic carbonates of the Bighorn and Madison formations cropping out in the Bighorn Basin, Wyoming, USA. The inversion technique applied to bedding-parallel stylolites allows determination of the absolute magnitude of the vertical stress experienced at the time dissolution stops along the pressure-solution planes. At the basin scale, reconstructed vertical stress magnitudes range from 19 ± 2 MPa to 35 ± 4 MPa in the Bighorn Fm, and from 12 ± 2 MPa to 37 ± 4 MPa in the Madison Fm. Once converted into depth and compared with up-to-date basin models of burial and contractional history, the dataset highlights that bedding-parallel stylolites accommodated compaction from ca. 220 Ma until ca. 90 Ma, i.e. until stress build-up related to the Sevier contraction made the maximum horizontal principal stress high enough to overcome the vertical principal stress. This study is key to illustrate how stylolites can be used to consistently access paleoburial and to unravel both stress evolution and timing in foreland settings, and indicates that pressure-solution remains active throughout the carbonate deposition history. Highlights: Bedding parallel stylolites are used to reconstruct past vertical stress history in a contractional basin. Long-term burial history is unravelled with no assumption on the past geothermal gradient. Bedding-parallel stylolites are active until the horizontal stress magnitude overcomes the vertical stress magnitude.